Factors Affecting the Quality of Cooperative Financial Statements - Tria Khoiron Nisa Saputra; Budi Septiawan; Endra Herdiansyah (RTTM, 2025)
Many cooperatives remain unable to prepare financial statements in accordance with applicable accounting standards, raising concerns about the quality and reliability of their financial reporting. This study aims to analyze and examine the influence of key factors—namely human resource capacity, accounting knowledge, and the use of information technology—on the quality of financial statements quality. Employing a descriptive-verification method with a quantitative approach, the research was conducted on 48 respondents comprising cooperative administrators and financial officers. Data were collected through questionnaires and analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) technique. The results reveal that both human resource capacity and accounting knowledge have a significant positive impact on the quality of financial statements quality. In contrast, the use of information technology was found to have no significant positive effect. These findings suggest that improving the competencies and accounting literacy of cooperative personnel plays a more crucial role than technological adoption alone in enhancing financial reporting quality. The study contributes to the understanding of internal factors that affect financial statement quality in cooperatives and offers insights for policymakers and cooperative stakeholders seeking to strengthen financial management practices.